Seminal plasma arising from the whole boar sperm-rich fraction increases the stability of sperm membrane after thawing - Torres, M. A.; Ravagnani, G. M.; Leal, D. F.; Martins, S. M. M. K.; Muro, B. B. D.; Meirelles, F. V.; Papa, F. O. [UNESP]; Dell'aqua Junior, J. A. [UNESP]; Alvarenga, M. A. [UNESP]; Moretti, A. S.; De Andrade, A. F. C. (Amer Soc Animal Science, 2016)
Boar spermatozoa arising from the sperm-rich ejaculate fraction are reported to have a more stable plasma membrane and are more resistant to cold shock and premature acrosome reaction than spermatozoa from the whole ejaculate. Furthermore, seminal plasma (SP) can increase the cryotolerance of boar spermatozoa, and in other domestic species, it has the ability to reverse cryopreservation damage. This study aimed to evaluate the effects of boar SP arising from the whole sperm-rich ejaculate fraction (SP-SRF) on the integrity, stability, and peroxidation of sperm membranes after thawing. Each ejaculate (n = 24) was divided among 4 treatments: control (CT), centrifuged and suspended in autologous SP-SRF (CS), centrifuged with withdrawn SP-SRF (CW), and post-thawed SP arising from the whole sperm-rich fraction addition to CW (CWSP). After thawing, all treatments were incubated for 5, 60, and 120 min and were analyzed for membrane integrity, fluidity, and peroxidation by flow cytometer. The absence of SP-SRF increased the lipid disorder (P < 0.05) but had no effect on lipid peroxidation (P > 0.05) or membrane integrity (P > 0.05). However, the increase in lipid disorder by withdrawal of SP-SRF was reversed by SP-SRF addition (P < 0.05) to the post-thawing medium, whereas plasma and acrosomal membrane integrity (P > 0.05) and lipid peroxidation (P > 0.05) were unchanged. In conclusion, despite the centrifugation effects, the addition of SP arising from the whole sperm-rich fraction to post-thawed boar semen decreased sperm lipid disorder without an influence of the sperm membrane integrity and peroxidation.
Keywords: lipid disorder; lipid peroxidation; membrane integrity; seminal plasma; spermatozoa; swine